Evaluation of Adverse Drug Reactions in Pediatric Patients - Mandha, Mallesh; Reddy, K. Purushothama; Reddy, K. Ravindra (Indian Journal of Pharmacy Practice)
To evaluate the occurrence of Adverse Drug Reactions (ADRs) in the children who are hospitalized, the follow-up processes resulting from it and to evaluate the reporting of ADRs by health care professionals. The occurrence of ADRs among hospitalized children has not been well established. As the clinical trials involving neonates, infants and children are absent or limited, the safety and tolerability of drugs are not well established among them hence the pharmacological actions of drugs are not similar to those identified for adults. A prospective observational study was conducted between June 2012 and March 2013 at Rajiv Gandhi Institute of Medical sciences (RIMS) an 800 bedded tertiary care teaching hospital, Kadapa. A total of 109 ADRs were identified. The most of the ADRs were mild(54.12%), severe were least (12.85%) and the moderate were between them (20.2%). Maximum of ADRs (89.91%, n-98) identified were predictable and least (10.09%, n-11) were non-predictable. Highest incidence is of GI effects (22.02%) and the lowest is of tinnitus (0.91%).ADRs rated high in severity resulted from anti convulsants (phenobarbitone), lowest resulted from Anti-malarials (Artemether). Mortality rate was restricted to 1.83% (n-2). Maximum ADRs were reported by pharmacists (89%), and least by patient representatives (2%). Measurements to be undertaken for the improvement of the detection and reporting of adverse drug reactions by all health care professionals, to enhance the impact of understanding these reactions in children and to promote the safe use of drugs in the pediatric patients.
Keywords: Adverse drug reactions; Pediatrics; Pediatric safety